The influence of gender and political connections on tax avoidance in Indonesia - Kurniasari, Elvira Putri; Setiawati, Erma (Institute of Computer Science (IOCS), 2024)
Tax avoidance is a legal strategy employed to evade taxation by exploiting various loopholes in tax regulations, engaging in transactions with the primary objective of circumventing tax payments. This study aims to assess the impact of gender diversity and political connections on tax avoidance within manufacture companies listed on the Indonesia Stock Exchange during the period 2019-2021. The research utilized purposive sampling, involving 205 companies that met the specified criteria. Multiple linear regression analysis was employed as the analytical method. The empirical findings reveal that gender divestiy significantly influence tax avoidance. On the other hand, political connections show no effect on tax avoidance.